A constituição do campo psiquiátrico: duas perspectivas antagônicas The formation of the field of psychiatry: two opposing perspectives - Jairo Roberto de Almeida Gama (História, Ciências, Saúde: Manguinhos)
Analisa duas concepções antagônicas sobre a constituição do campo psiquiátrico. A perspectiva prevalente no Brasil, a foucaultiana, é contrastada com a perspectiva de Gauchet e Swain. Para a tarefa são abordadas duas obras de Foucault, A história da loucura e O poder psiquiátrico, e a obra de Gauchet e Swain, Madness and democracy. Propõe que as concepções de base sobre o que é e como se construiu o campo teórico psiquiátrico definem as estratégias políticas e assistenciais de uma sociedade na sua relação com a loucura. Aponta as consequências diversas que essas abordagens trazem para a reforma psiquiátrica brasileira. The article analyzes two opposing views of the formation of the psychiatric field: the Foucauldian perspective, which holds sway in Brazil, and the perspective of Gauchet and Swain. Two works by Foucault (History of Madness and Psychiatric Power) are contrasted with Madness and Democracy, by the latter authors. It is argued that a society's political and assistance strategies about madness are shaped by the conceptual bases defining what constitutes the field of psychiatric theory and how it was formed. The article calls attention to the diverse consequences that these two approaches may have on the reform of Brazilian psychiatry.